Analysis of rebranding strategies in companies experiencing crisis - Anindya Putri Utami; Eva Fachria; Reni Nur Arifah; Putri Aryo Jelang FK; Yetty Yuliany Kusumaningrum; Randika Shafly Fawwaz (Priviet Social Sciences Journal, 2026)
This study aims to analyze the impact of rebranding strategies on brand image and company performance in organizations facing crises. In a dynamic and competitive business environment, rebranding is understood as a strategic transformation process that goes beyond changes in logos or brand names and encompasses the renewal of the company’s vision, mission, values, and brand communication. This study employs a quantitative approach using a survey method targeting consumers aware of the company’s rebranding process after the crisis. The sampling technique used is purposive sampling, with data collected through a Likert-scale questionnaire. The results indicate that rebranding strategies positively and significantly affect company performance. Brand image plays a dominant role in strengthening positive consumer perceptions and enhancing loyalty and trust in the company. The findings also suggest that consistent, honest, and transparent brand communication is a key factor in the success of rebranding initiatives in the hospitality industry. Holistic rebranding accompanied by internal reforms can restore corporate reputation and improve business performance in the post-crisis period. This study contributes theoretically to the development of marketing management literature and serves as a practical reference for companies in designing effective rebranding strategies for image recovery and performance enhancement.